Analisis Hasil Kegiatan Interview Mahasiswa Semester 2A Program Studi Bahasa dan Sastra Indonesia STKIP PGRI Lubuklinggau - Agung Nugroho (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2017)
The purpose of this study is to describe the results of the second semester/A, College of Teacher Training and Education Activities Teachers Association of Indonesia, City of Lubuklinggau in 2016 on systematic aspects, covering (Opening, content and closing) and attitude of interviewing (Neutral, Friendly, fair and Luwes). This study used descriptive qualitative method. The results of this study is a description of the analysis of the results of interview activities that covers, Systematics and attitude at the time of interview. Based on the results of the research can be seen that the errors that are in the results of student interview activities. Indonesian Language and Literature Education is still very high. Errors contained from the results of student interview activity, broadly covered, systematic enough categorized, as well as the attitude of the interview is still in enough category. The dominating factor is the experience of the students is still very low, this will be the attention of the author as a lecturer pengampu course to actively train interview activities so that kedepanya can be better. Keywords: Prying, Interviewing.